Determination of Profit Change through Current Ratio, Debt to Equity Ratio, Return on Equity, and Total Asset Turnover in Manufacturing Companies Listed in Indonesia - Azaluddin; Hanifa, Lia (Institute for Research and Community Service, 2024)
This study analyzes the determination of profit change through financial ratios, including Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Total Asset Turnover (TATO), in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research aims to identify the extent to which these financial ratios influence changes in company profitability. Using a quantitative approach with an explanatory design, data were collected from 20 manufacturing companies that consistently published complete financial statements throughout the observation period. The analytical technique employed descriptive statistics and multiple linear regression analysis, supported by classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that the regression model fulfills all classical assumptions, ensuring its validity and reliability. Empirical findings indicate that Return on Equity (ROE) and Total Asset Turnover (TATO) have a significant positive effect on profit change, while Current Ratio (CR) and Debt to Equity Ratio (DER) have a weaker but still relevant influence. The coefficient of determination (R²) value of 0.68 indicates that 68 percent of profit variation can be explained by these financial ratios, while the remaining 32 percent is influenced by other external factors such as operational efficiency and market conditions.